Strategi Manajemen KPSPAMS Tirta Mulya Dalam Penerapan Iuran Pelanggan Air Minum Untuk Desa Keberlanjutan PAMSIMAS - Hartono, Rudi (Jurnal Adminitrasi Bisnis Nusantara, 2022)
Achieving the SDG's target of providing access to drinking water for the entire community requires effort and hard work from the government. Several drinking water infrastructure development programs have been launched by the government to meet basic service needs for the community, especially in rural areas. However, in the development phase of the construction phase, the developed Village SPAM experienced different developments. This study aims to determine the sustainability of the community based rural drinking water supply system and the factors that influence it sustainability of the system. This research uses a qualitative approach with a case study method. The research design used is an olistic multicase study with two research villages, namely Piji Village and Gintungan Village. The results of the Continuation of SPAM in Mekar Jaya Village since 2017 have become part of one of the BUMDES business units in Mekar Jaya Village. Home connected services have grown from SR 50 at the start of operations to SR 235 in 2018. And in inkind since PAMSIMAS 1 support from HID and PAMSIMAS III. Likewise, they also accept that the residents are willing to pay the water usage fee of Rp. 1.500/m3 and a management fee of Rp. 2,000/month. The community did not object because they considered it the amount of water they received.